Optical glass, glass preforms, optical components and optical instruments
By rationally designing the components of optical glass, the problem of insufficient anti-crystallization performance of optical glass during the secondary pressing process is solved, high anti-crystallization performance and low negative special dispersion are achieved, which reduces processing costs and improves the quality of the finished product. quality.
Patent Information
- Application Number
- CN202211554294.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-06
AI Technical Summary
The existing optical glass has insufficient crystallization resistance during the secondary pressing process, resulting in high processing costs and unstable finished product quality.
Through the reasonable design of optical glass components, it contains SIO2, B2O3, ZRO2, NB2O5 and alkaline metal oxides, controlling refractive index, Beibei, and relative parts of color dispersion to ensure that the glass has excellent anticorbine performance and low negative direction Special colors.
The high anti -definition performance of optical glass in the process of secondary pressure has reduced the processing cost of processing, and the geometric accuracy and imaging quality of the finished product is improved.
Smart Images

Figure BDA0003982599180000131 
Figure BDA0003982599180000141 
Figure BDA0003982599180000142
Abstract
Description
Technical Field
[0001] The invention relates to an optical glass, in particular to an optical glass with excellent anti-crystallization performance and negative special dispersion. Background Art
[0002] In long focal length, large field of view and high precision optical systems, secondary spectrum is the main factor affecting the image quality. Correcting the secondary spectrum is a prominent problem in the design of long focal length optical systems and is also a relatively difficult problem to solve. The use of special dispersion glass in combination with other glasses can reduce the number of glass lenses, simplify the structure of the optical system, and especially eliminate the secondary spectrum, improving the image quality and geometric accuracy. The special dispersion performance characterization parameters of optical glass are mainly the relative partial dispersion deviation value △P g,F , △P g,F The larger the absolute value, the greater the special dispersion of the optical glass, and the more conducive it is to eliminating the secondary spectrum of the optical system.
[0003] Secondary pressing has the advantages of low production cost, low production difficulty, and convenience for mass production, and is widely used in the production of glass components. Secondary pressing is a production method in which the glass material is placed in a mold and heated to above the softening point, and then the glass material is pressed into a predetermined shape by applying pressure. This production method often requires heating the glass to 100 to 200°C above the transition temperature. At this time, the glass already has a certain fluidity. If the anti-crystallization performance of the glass is not good, the glass will be at risk of crystallization and scrap during the secondary pressing process. In order to reduce the processing cost of optical glass, optical glass is required to have higher anti-crystallization performance to adapt to the widely used secondary pressing technology. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an optical glass with excellent anti-crystallization performance and low negative special dispersion.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Optical glass, the components of which, expressed in molar percentage, contain: SiO2+B2O3+Al2O3: 40-75%; ZrO2: 1.5-10%; Nb2O5: 5-12%; Li2O: 2.5-38%; Na2O: 3.5-24%.
[0007] (2) The optical glass according to (1), wherein the components, expressed in molar percentage, further contain: BaO: 0-4%; and / or SrO: 0-7%; and / or CaO: 0-13%; and / or MgO: 0-9.5%; and / or ZnO: 0-9.5%; and / or La2O3: 0-2.5%; and / or Gd2O3: 0-2%; and / or Y2O3: 0-3%; and / or Yb2O3: 0-2%; and / or TiO2: 0-9.5%; and / or WO3: 0-4%; and / or Bi2O5: 0-2%; and / or Ta2O5: 0-3%; and / or K2O: 0-8%; and / or Sb2O3: 0-0.5%.
[0008] (3) Optical glass, the components of which include SiO2, B2O3, ZrO2, Nb2O5 and alkali metal oxides, wherein the refractive index of the optical glass is n d is 1.62~1.78, Abbe number v d 34~44, relative partial dispersion deviation value △P g,F Below -0.00300.
[0009] (4) The optical glass according to (3), wherein the components, expressed in molar percentage, are: SiO2+B2O3+Al2O3: 40-75%; and / or ZrO2: 1.5-10%; and / or Nb2O5: 5-12%; and / or Li2O: 2.5-38%; and / or Na2O: 3.5-24%; and / or BaO: 0-4%; and / or SrO: 0-7%; and / or CaO: 0-13%; and / or MgO: 0~9.5%; and / or ZnO: 0~9.5%; and / or La2O3: 0~2.5%; and / or Gd2O3: 0~2%; and / or Y2O3: 0~3%; and / or Yb2O3: 0~2%; and / or TiO2: 0~9.5%; and / or WO3: 0~4%; and / or Bi2O5: 0~2%; and / or Ta2O5: 0~3%; and / or K2O: 0~8%; and / or Sb2O3: 0~0.5%.
[0010] (5) The optical glass according to any one of (1) to (4), wherein the components are expressed in molar percentage, wherein: SiO2+Al2O3+ZrO2: 40-70%, preferably SiO2+Al2O3+ZrO2: 40-60%, more preferably SiO2+Al2O3+ZrO2: 43-56%; and / or Nb2O5+ZrO2: 7-20%, preferably Nb2O5+ZrO2: 9-18%, more preferably Nb2O5+ZrO2: 10-16%; and / or TiO2+WO3+Bi2O3: 0-10%, preferably TiO2+WO3+Bi2O3 : 0-7%, more preferably TiO2+WO3+Bi2O3: 0-4%; and / or Rn2O: 15-60%, preferably Rn2O: 20-50%, more preferably Rn2O: 25-36%; and / or RO: 0-13%, preferably RO: 0-11%, more preferably RO: 0-7%; and / or Re2O3: 0-7%, preferably Re2O3: 0-3%, wherein Rn2O is the total content of Li2O, Na2O and K2O, Re2O3 is the total content of La2O3, Gd2O3 and Y2O3, and RO is the total content of BaO, SrO, CaO and MgO.
[0011] (6) The optical glass according to any one of (1) to (4), wherein the components are expressed in molar percentages, wherein: (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.6 to 4.5, preferably (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.8 to 3.0, more preferably (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 1.0 to 2.2; and / or (SiO2+B2O3) / ZrO2 is 5.0 to 25.0, preferably (SiO2+B2O3) / ZrO2 is 5.0 to 25.0, / ZrO2 is 6.0 to 20.0, and more preferably (SiO2 + B2O3) / ZrO2 is 7.0 to 17.0; and / or (SiO2 + B2O3 + ZrO2) / Rn2O is 0.8 to 4.5, and preferably (SiO2 + B2O3 + ZrO2) / Rn2O is 1.1 to 3.8, and more preferably (SiO2 + B2O3 + ZrO2) / Rn2O is 1.4 to 2.7, wherein Rn2O is the total content of Li2O, Na2O and K2O, and RO is the total content of BaO, SrO, CaO and MgO.
[0012] (7) The optical glass according to any one of (1) to (4), wherein the components are expressed in molar percentage, wherein: SiO2+B2O3+Al2O3: 45-60%; and / or ZrO2: 2.5-8.5%, preferably ZrO2: 3-7.5%; and / or Nb2O5: 6-11%, preferably Nb2O5: 7-10%; and / or Li2O: 7.5-30%, preferably Li2O: 12-23%; and / or Na2O: 7.5-22%, preferably Na2O: 10.5-18.5%; and / or BaO: 0-2.5%, preferably BaO: 0-1%; and / or SrO: 0-3.5%; and / or C aO: 0-10.5%, preferably CaO: 0-7%; and / or MgO: 0-5.5%; and / or ZnO: 0-4.5%, preferably ZnO: 0-2%; and / or La2O3: 0-1.5%; and / or Gd2O3: 0-1%; and / or Y2O3: 0-1.5%; and / or Yb2O3: 0-1%; and / or TiO2: 0-6.5%, preferably TiO2: 0-4%; and / or WO3: 0-2%; and / or Ta2O5: 0-2%; and / or K2O: 0-6%, preferably K2O: 0-4%; and / or Sb2O3: 0-0.25%, preferably Sb2O3: 0-0.1%.
[0013] (8) An optical glass according to any one of (1) to (4), wherein the components are expressed in molar percentage, wherein: SiO2: 32 to 58%, preferably SiO2: 36 to 54%, more preferably SiO2: 40 to 49%; and / or B2O3: 4 to 16%, preferably B2O3: 5.5 to 14%, more preferably B2O3: 6.5 to 12%; and / or Al2O3: 0 to 7%, preferably Al2O3: 0 to 4%.
[0014] (9) The optical glass according to any one of (1) to (4), which does not contain Al2O3; and / or does not contain SrO; and / or does not contain MgO; and / or does not contain La2O3; and / or does not contain Gd2O3; and / or does not contain Y2O3; and / or does not contain Yb2O3; and / or does not contain WO3; and / or does not contain Bi2O5; and / or does not contain Ta2O5.
[0015] (10) The refractive index n of the optical glass according to any one of (1) to (4) d is 1.62 to 1.78, preferably 1.64 to 1.75, more preferably 1.66 to 1.70, and the Abbe number v d It is 34-44, preferably 35-42, and more preferably 36-40.
[0016] (11) The relative partial dispersion deviation value ΔP of the optical glass according to any one of (1) to (4)g,F is below -0.00300, preferably below -0.00350, more preferably below -0.00410; and / or the density ρ of the optical glass is 3.25 g / cm 3 Below, preferably 3.15g / cm 3 Below, more preferably 3.05g / cm 3 and / or the number A of optical glass crystallizations is 5 or less, preferably 2 or less, and more preferably 0.
[0017] (12) A glass preform made of the optical glass described in any one of (1) to (11).
[0018] (13) An optical element is made of the optical glass described in any one of (1) to (11), or is made of the glass preform described in (12).
[0019] (14) An optical instrument comprising the optical glass described in any one of (1) to (11) and / or the optical element described in (13).
[0020] The beneficial effects of the present invention are: through reasonable component design, the glass of the present invention has lower negative specific dispersion and excellent anti-crystallization performance. DETAILED DESCRIPTION
[0021] The following is a detailed description of the embodiments of the optical glass of the present invention, but the present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention is not limited thereto. In the following content, the optical glass of the present invention is sometimes referred to as glass.
[0022] Ⅰ. Optical glass
[0023] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in mole percentage (mol%), that is, the content and total content of each component are expressed in mole percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total molar amount of the oxide material is taken as 100%.
[0024] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0025] <Essential Components and Optional Components>
[0026] SiO2 is a component of glass network generator, which has the effect of improving the chemical stability and weather resistance of glass and maintaining the anti-crystallization performance of glass. If the content of SiO2 is lower than 32%, it is difficult to achieve the above effect. Therefore, the lower limit of SiO2 content is 32%, preferably the lower limit of SiO2 content is 36%, and more preferably the lower limit of SiO2 content is 40%. If the content of SiO2 is higher than 58%, the glass becomes very difficult to melt, and it is difficult to obtain the optical constants desired by the present invention, and the negative relative partial dispersion deviation value increases. Therefore, the upper limit of SiO2 content is 58%, preferably the upper limit is 54%, and more preferably the upper limit is 49%.
[0027] B2O3 is a component of the glass network former, which can maintain the anti-crystallization performance of the glass, reduce the difficulty of glass chemical processing, and reduce the high-temperature viscosity and transition temperature of the glass. If the content of B2O3 is lower than 4%, it is difficult to achieve the above-mentioned effect. Therefore, the lower limit of the B2O3 content is 4%, preferably the lower limit of the B2O3 content is 5.5%, and more preferably the lower limit of the B2O3 content is 6.5%. If the content of B2O3 is higher than 16%, the B2O3 in the glass tends to be in a [BO3] coordination state, which will increase the negative relative partial dispersion deviation value of the glass, making it difficult to obtain the optical constants desired by the present invention. Therefore, the upper limit of the B2O3 content is 16%, preferably the upper limit is 14%, and more preferably the upper limit is 12%.
[0028] Al2O3 can improve the thermal stability of glass and maintain the anti-crystallization performance of glass, but it will increase the melting temperature and high temperature viscosity of glass, increasing the difficulty of production. When the Al2O3 content exceeds 7%, the glass tends to have poor melting properties and reduced devitrification resistance. Therefore, the content of Al2O3 in the present invention is 0-7%, preferably 0-4%, and more preferably no Al2O3.
[0029] In some embodiments of the present invention, by controlling the total content of SiO2, B2O3 and Al2O3 SiO2+B2O3+Al2O3 in the range of 40-75%, it is beneficial to maintain the anti-crystallization performance of the glass and maintain the relative partial dispersion deviation value of the glass within the design range. Therefore, preferably SiO2+B2O3+Al2O3 is 40-75%, and more preferably SiO2+B2O3+Al2O3 is 45-60%.
[0030] BaO is a low-cost raw material that is easy to obtain and can improve the refractive index of glass. However, BaO is not good for reducing the density of glass. In addition, when the BaO content is too high, the weather resistance of the glass decreases rapidly. Therefore, the BaO content is limited to 0-4%, preferably 0-2.5%, and more preferably 0-1%.
[0031] An appropriate amount of SrO can improve the weather resistance of glass and reduce the density of glass. However, since the raw material of SrO is expensive and a high content of SrO leads to an increase in the cost of glass, the content of SrO is limited to 0-7%, preferably 0-3.5%, and more preferably no SrO.
[0032] CaO can improve the hardness, mechanical strength and weather resistance of glass. More importantly, compared with BaO and SrO, CaO is more beneficial to reducing the density of glass. In addition, CaO is also beneficial to the control and regulation of optical constants during the production process. However, when the CaO content is too high, it makes it difficult to melt the glass, and a layer of calcium-rich hard shell is easily formed in the melting pool during the production process. Therefore, the CaO content is limited to 0-13%, preferably 0-10.5%, and more preferably 0-7%.
[0033] MgO helps to improve the weather resistance of glass, but when the content is high, the refractive index of the glass is difficult to meet the design requirements, the anti-crystallization performance and stability of the glass are reduced, and the cost of the glass rises rapidly. Therefore, the MgO content is limited to 0-9.5%, preferably 0-5.5%, and more preferably no MgO is contained.
[0034] BaO, SrO, CaO, and MgO are alkaline earth metal oxides, which have the effect of improving the thermal stability and devitrification resistance of glass. However, when the content of these glass components is too much, the density of the glass increases, it is difficult to obtain the desired optical constants, and the thermal stability and devitrification resistance of the glass decrease. Therefore, the total content of alkaline earth metal oxides RO is preferably controlled within the range of 0 to 13%, more preferably 0 to 11%, and further preferably 0 to 7%.
[0035] ZnO can improve the acid resistance stability of glass, enhance the weather resistance of glass, and reduce the transition temperature of glass. However, when its content is too high, the density of glass increases, and it will increase the corrosion of platinum vessels during the smelting process and reduce the service life of the furnace. Therefore, the content of ZnO in the glass of the present invention is 0-9.5%, preferably 0-4.5%, and more preferably 0-2%.
[0036] ZrO2 has the effect of improving the weather resistance of glass and enhancing the anti-crystallization performance of glass. At the same time, ZrO2 in glass can significantly reduce the relative partial dispersion deviation value of glass. However, the solubility of ZrO2 in the glass of this system is not high. When the content is too much, it is easy to be free from the glass system to form crystallization nuclei, which leads to the deterioration of the anti-crystallization performance of the glass. Therefore, the content of ZrO2 in the present invention is 1.5-10%, preferably 2.5-8.5%, and more preferably 3-7.5%.
[0037] SiO2, Al2O3 and ZrO2 can all improve the weather resistance of glass, and SiO2, Al2O3 and ZrO2 are also difficult to melt components in the present invention. Through a large number of experimental studies by the inventors, it is found that in some embodiments, when the total content of SiO2, Al2O3 and ZrO2 SiO2+Al2O3+ZrO2 is in the range of 40-70%, the glass can obtain both excellent weather resistance and good production performance. Therefore, it is preferred that SiO2+Al2O3+ZrO2 is 40-70%, more preferably SiO2+Al2O3+ZrO2 is 40-60%, and further preferably SiO2+Al2O3+ZrO2 is 43-56%.
[0038] La2O3 is a high refractive and low dispersion component, which can greatly reduce the relative partial dispersion of glass in glass, but when its content is too high, the dispersion of glass is reduced, and it is difficult to achieve the desired optical constants of the present invention. Therefore, the content of La2O3 in the present invention is 2.5% or less, preferably 1.5% or less, and more preferably no La2O3 is contained.
[0039] Gd2O3 is a high refractive and low dispersion component, which can reduce the relative partial dispersion of glass in glass, but the expensive raw material price limits the use of Gd2O3 in glass. Therefore, the content of Gd2O3 is 0-2%, preferably 0-1%, and more preferably no Gd2O3 is contained.
[0040] Y2O3 can improve the melting property of glass and also improve the weather resistance of glass, but when its content is too high, the glass is easy to lose transparency during the manufacturing process, and the dispersion of the glass is reduced, and the optical constants expected by the present invention cannot be achieved. Therefore, the content of Y2O3 is 0-3%, preferably 0-1.5%, and more preferably no Y2O3 is contained.
[0041] La2O3, Gd2O3 and Y2O3 can improve the refractive index and reduce the relative partial dispersion in glass, but if the content is too much, it will be difficult to achieve the desired optical constants of the present invention. Therefore, the total content of La2O3, Gd2O3 and Y2O3 in the present invention is preferably 0-7%, more preferably 0-3%, and more preferably no Re2O3.
[0042] Compared with La2O3, Gd2O3, and Y2O3, Yb2O3 has a larger molecular weight, so it increases the density of the glass. In addition, when the content of Yb2O3 is too high, the thermal stability of the glass decreases. In order to prevent the thermal stability of the glass from decreasing and suppress the increase in density, the content of Yb2O3 is limited to 0-2%, preferably 0-1%, and more preferably no Yb2O3 is contained.
[0043] Nb2O5 is an essential component of the glass of the present invention and is a key component to ensure that the glass has the desired optical constants and negative relative partial dispersion deviation value characteristics. The inventors have found through intensive research that if the content of Nb2O5 is too much, the anti-crystallization performance of the glass will deteriorate. Therefore, the content of Nb2O5 in the present invention is 5-12%, preferably 6-11%, and more preferably 7-10%.
[0044] Nb2O5 and ZrO2 are key components for maintaining the low relative partial dispersion performance of the present invention. In some embodiments of the present invention, when the total content of Nb2O5 and ZrO2, Nb2O5+ZrO2, is controlled within the range of 7 to 20%, the refractive index, dispersion and relative partial dispersion deviation value of the glass can better meet the design requirements. Therefore, preferably Nb2O5+ZrO2 is 7 to 20%, more preferably Nb2O5+ZrO2 is 9 to 18%, and further preferably Nb2O5+ZrO2 is 10 to 16%.
[0045] TiO2 can increase the refractive index and dispersion of glass, improve the anti-crystallization performance of glass, and reduce the density of glass. However, TiO2 in glass will cause a sharp increase in relative partial dispersion. When the TiO2 content in glass is higher than 9.5%, the low negative relative dispersion deviation characteristics of the glass are difficult to meet the design requirements. Therefore, the content of TiO2 is 0 to 9.5%, preferably 0 to 6.5%, and more preferably 0 to 4%.
[0046] WO3 can improve the refractive index and dispersion of glass, but will cause the negative relative dispersion deviation of glass to increase sharply, and will also cause the light transmittance of glass to decrease. In the present invention, the WO3 content is 0-4%, preferably 0-2%, and more preferably no WO3 is contained.
[0047] Bi2O3 can improve the refractive index and dispersion of glass, but it will cause the negative relative dispersion deviation of glass to rise sharply. In addition, Bi2O3 will corrode platinum vessels seriously during the smelting process, so its content is limited to less than 2%, and it is preferred not to contain Bi2O3.
[0048] TiO2, WO3 and Bi2O3 all have the effect of increasing the refractive index and dispersion of glass, but all of them will cause the negative relative dispersion deviation value of glass to rise sharply. Therefore, in the present invention, the combined content of TiO2, WO3 and Bi2O3 is preferably 0-10%, more preferably 0-7%, and further preferably 0-4%.
[0049] Ta2O5 is a high-refractive and high-dispersion component that can reduce the relative partial dispersion value of glass. At the same time, Ta2O5 can improve the anti-crystallization performance of glass and enhance the stability of glass. However, the expensive raw material cost greatly limits the use of Ta2O5. The content of Ta2O5 in the present invention is 0-3%, preferably 0-2%, and more preferably no Ta2O5 is contained.
[0050] Li2O belongs to alkali metal oxides and is a key component in the present invention that reduces the difficulty of glass production. Li2O can be used as a flux to reduce the difficulty of glass chemical production. At the same time, Li2O can reduce the high-temperature viscosity and transition temperature of glass, making glass production and processing easier. The inventors have devoted themselves to research and found that by adding Li2O to the glass and utilizing the accumulation effect of Li2O, the weather resistance of the glass can be improved. However, if the content of Li2O is too high, the acid resistance of the glass will decrease. Therefore, in the glass of the present invention, the content of Li2O is 2.5-38%, preferably 7.5-30%, and more preferably 12-23%.
[0051] Na2O and K2O can also reduce the chemical temperature and high temperature viscosity of glass, and reduce the difficulty of glass production. However, compared with the accumulation effect of Li2O, Na2O and K2O will cause the silicon network structure of glass to break and increase the relative partial dispersion of glass. Therefore, the content of Na2O in the glass of the present invention is 3.5-24%, preferably 7.5-22%, and more preferably 10.5-18.5%; the content of K2O is 0-8%, preferably 0-6%, and more preferably 0-4%.
[0052] Li2O, Na2O and K2O are all alkali metal oxides, which can reduce the difficulty of glass production, but excessive content will reduce the chemical stability of glass. Therefore, in the present invention, the total content of Li2O, Na2O and K2O is preferably controlled within the range of 15 to 60%, more preferably 20 to 50%, and further preferably 25 to 36%.
[0053] The inventors have conducted a large number of experimental studies and found that alkali metal oxides Rn2O and alkaline earth metal oxides RO can promote the melting of SiO2, Al2O3 and ZrO2, and reduce the difficulty of melting glass. Further, in some embodiments, when the ratio of the total content of SiO2, Al2O3 and ZrO2 SiO2+Al2O3+ZrO2 to the content of Rn2O+RO (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is between 0.6 and 4.5, the glass can obtain excellent melting performance and anti-crystallization performance. Therefore, the preferred value of (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.6 to 4.5, the more preferred value of (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.8 to 3.0, and the further preferred value of (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 1.0 to 2.2.
[0054] The silicate glass network structure has a weak carrying capacity for ZrO2. When the ZrO2 content is too high, it is easy to precipitate and form stones during the melting process. Through a large number of experimental studies by the inventors, it is found that in some embodiments, B2O3 can improve the carrying capacity of silicate glass for ZrO2. When the ratio between the total content of SiO2 and B2O3 and the content of ZrO2 (SiO2+B2O3) / ZrO2 is in the range of 5.0 to 25.0, the carrying capacity of the glass system of the present invention for ZrO2 can be improved, and the chemical stability of the glass can be improved, and the anti-crystallization performance of the glass can be improved. Therefore, it is preferred that (SiO2+B2O3) / ZrO2 is 5.0 to 25.0, more preferably (SiO2+B2O3) / ZrO2 is 6.0 to 20.0, and further preferably (SiO2+B2O3) / ZrO2 is 7.0 to 17.0.
[0055] Through a large number of experimental studies by the inventors, it was found that in some embodiments, the alkali metal oxide Rn2O can cooperate with B2O3 to improve the carrying capacity of glass for ZrO2. When the ratio between the content of SiO2+B2O3+ZrO2 and the content of Rn2O (SiO2+B2O3+ZrO2) / Rn2O is in the range of 0.8 to 4.5, the carrying capacity of the glass system of the present invention for ZrO2 can be improved, and the anti-crystallization performance of the glass can be improved. Therefore, it is preferred that (SiO2+B2O3+ZrO2) / Rn2O is 0.8 to 4.5, more preferably (SiO2+B2O3+ZrO2) / Rn2O is 1.1 to 3.8, and further preferably (SiO2+B2O3+ZrO2) / Rn2O is 1.4 to 2.7.
[0056] Sb2O3 can be used as a clarifier in the present invention to improve the clarification effect of the glass. Its content ranges from 0 to 0.5%, preferably from 0 to 0.25%, and more preferably from 0 to 0.1%.
[0057] <Components that should not be contained>
[0058] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0059] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0060] In order to achieve environmental friendliness, the optical glass of the present invention does not contain As2O3 and PbO. Although As2O3 has the effect of eliminating bubbles and preventing glass from being colored, the addition of As2O3 will increase the platinum corrosion of the glass on the furnace, especially the platinum furnace, causing more platinum ions to enter the glass, which has an adverse effect on the service life of the platinum furnace. PbO can significantly improve the high refractive index and high dispersion performance of the glass, but both PbO and As2O3 are substances that cause environmental pollution.
[0061] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0062] Next, the properties of the optical glass of the present invention will be described.
[0063] <Refractive Index and Abbe Number>
[0064] Refractive index of optical glass (n d ) and Abbe number (v d ) Tested according to the method specified in GB / T 7962.1-2010.
[0065] In some embodiments, the refractive index (n d) is 1.62 to 1.78, preferably 1.64 to 1.75, and more preferably 1.66 to 1.70.
[0066] In some embodiments, the Abbe number (v d ) is 34-44, preferably 35-42, and more preferably 36-40.
[0067] <Relative partial dispersion deviation value>
[0068] Relative partial dispersion deviation value of optical glass (△P g,F ) is calculated as: △P g,F =(n g -n F ) / (n F -n C )-0.6457+0.001703v d Where n g 、n F With n C Tested according to the method specified in GB / T 7962.1-2010.
[0069] In some embodiments, the relative partial dispersion deviation value ΔP of the optical glass of the present invention is g,F is -0.00300 or less, preferably ΔP g,F is -0.00350 or less, and more preferably ΔP g,F It is below -0.00410.
[0070] <density>
[0071] The density (ρ) of optical glass is tested according to the method specified in GB / T 7962.20-2010.
[0072] In some embodiments, the density (ρ) of the optical glass of the present invention is 3.25 g / cm 3 Below, preferably 3.15g / cm 3 Below, more preferably 3.05g / cm 3 the following.
[0073] <Anti-crystallization performance>
[0074] The test method for the anti-crystallization performance of optical glass is as follows: Place the sample in T g The sample was kept in a muffle furnace at +230°C for 15 minutes, taken out, and then cooled at room temperature. After double-sided polishing, the number of crystallized particles per cubic centimeter in the sample (A) was observed.
[0075] In some embodiments, the number of crystallizations (A) of the optical glass of the present invention is 5 or less, preferably 2 or less, and more preferably 0.
[0076] [Manufacturing method]
[0077] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and conventional processes, using composite salts (such as carbonates, nitrates, sulfates), hydroxides, oxides, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace at 1250-1450° C. for melting, and after clarification, stirring and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0078] Ⅱ. Glass preforms and optical elements
[0079] A glass preform can be made from the produced optical glass by means of grinding, or by means of compression molding such as re-hot pressing, precision stamping, etc. That is, a glass preform can be made by mechanical processing such as grinding and polishing the optical glass, or by making a preform for compression molding from the optical glass, re-hot pressing the preform and then grinding the preform to make a glass preform, or by precision stamping the preform made by grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0080] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0081] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0082] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0083] III. Optical instruments
[0084] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, vehicle-mounted equipment, video equipment, display equipment, and monitoring equipment.
[0085] Since the optical glass of the present invention has high refraction, high dispersion and low relative partial dispersion performance, it is particularly suitable for use in telephoto lenses and high-definition exchange lenses.
[0086] Example
[0087] <Optical Glass Example>
[0088] In order to further clearly explain and illustrate the technical solution of the present invention, the following non-limiting examples are provided. In this example, the optical glass manufacturing method described above is used to obtain the optical glass shown in Table 1 and Table 2. In addition, the properties of each glass are measured by the test method described in the present invention, and the measurement results are shown in Table 1 and Table 2.
[0089] Table 1.
[0090]
[0091]
[0092] Table 2.
[0093]
[0094]
[0095] <Glass Preform Example>
[0096] The glass obtained from optical glass examples 1 to 20 is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0097] <Optical Element Embodiment>
[0098] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the deformation inside the glass and perform fine adjustments so that the optical properties such as the refractive index reach the desired values.
[0099] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0100] <Optical Instrument Embodiment>
[0101] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. Optical glass, characterized in that: Its components, expressed in molar percentage, include: SiO2+B2O3+Al2O3: 40-75%; ZrO2: 1.5-10%; Nb2O5: 5-9.91%; Li2O: 2.5-38%; Na2O: 3.5-24%; SiO2: 32-58%; B2O3: 4-16%, (SiO2+B2O3) / ZrO2 is 7.0-17.
0.
2. The optical glass according to claim 1, characterized in that: Its components, expressed in molar percentage, also contain: BaO: 0-4%; and / or SrO: 0-7%; and / or CaO: 0-13%; and / or MgO: 0-9.5%; and / or ZnO: 0-9.5%; and / or La2O3: 0-2.5%; and / or Gd2O3: 0-2%; and / or Y2O3: 0-3%; and / or Yb2O3: 0-2%; and / or TiO2: 0-9.5%; and / or WO3: 0-4%; and / or Bi2O5: 0-2%; and / or Ta2O5: 0-3%; and / or K2O: 0-8%; and / or Sb2O3: 0-0.5%.
3. Optical glass, characterized in that: Its components include SiO2, B2O3, ZrO2, Nb2O5 and alkali metal oxides. Its components, expressed in molar percentage, include: SiO2+B2O3+Al2O3: 40-75%; ZrO2: 1.5-10%; Nb2O5: 5-9.91%; Li2O: 2.5-38%; Na2O: 3.5-24%; SiO2: 32-58%; B2O3: 4-16%, (SiO2+B2O3) / ZrO2 is 7.0-17.0, and the refractive index n of the optical glass is d is 1.62~1.78, Abbe number v d 34~44, relative partial dispersion deviation value △P g,F Below -0.00300.
4. The optical glass according to claim 3, characterized in that: Its components, expressed in molar percentage, contain: BaO: 0-4%; and / or SrO: 0-7%; and / or CaO: 0-13%; and / or MgO: 0-9.5%; and / or ZnO: 0-9.5%; and / or La2O3: 0-2.5%; and / or Gd2O3: 0-2%; and / or Y2O3: 0-3%; and / or Yb2O3: 0-2%; and / or TiO2: 0-9.5%; and / or WO3: 0-4%; and / or Bi2O5: 0-2%; and / or Ta2O5: 0-3%; and / or K2O: 0-8%; and / or Sb2O3: 0-0.5%.
5. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, among which: SiO2+Al2O3+ZrO2: 40-70%; and / or Nb2O5+ZrO2: 7-18%; and / or TiO2+WO3+Bi2O3: 0-10%; and / or Rn2O: 15-60%; and / or RO: 0-13%; and / or Re2O3: 0-7%, wherein Rn2O is the total content of Li2O, Na2O and K2O, Re2O3 is the total content of La2O3, Gd2O3 and Y2O3, and RO is the total content of BaO, SrO, CaO and MgO.
6. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: SiO2+Al2O3+ZrO2: 40-60%; and / or Nb2O5+ZrO2: 9-18%; and / or TiO2+WO3+Bi2O3: 0-7%; and / or Rn2O: 20-50%; and / or RO: 0-11%; and / or Re2O3: 0-3%, wherein Rn2O is the total content of Li2O, Na2O and K2O, Re2O3 is the total content of La2O3, Gd2O3 and Y2O3, and RO is the total content of BaO, SrO, CaO and MgO.
7. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, among which: SiO2+Al2O3+ZrO2: 43-56%; and / or Nb2O5+ZrO2: 10-16%; and / or TiO2+WO3+Bi2O3: 0-4%; and / or Rn2O: 25-36%; and / or RO: 0-7%, wherein Rn2O is the total content of Li2O, Na2O and K2O, Re2O3 is the total content of La2O3, Gd2O3 and Y2O3, and RO is the total content of BaO, SrO, CaO and MgO.
8. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.6-4.5; and / or (SiO2+B2O3+ZrO2) / Rn2O is 0.8-4.5, wherein Rn2O is the total content of Li2O, Na2O and K2O, and RO is the total content of BaO, SrO, CaO and MgO.
9. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 0.8-3.0; and / or (SiO2+B2O3+ZrO2) / Rn2O is 1.1-3.8, wherein Rn2O is the total content of Li2O, Na2O and K2O, and RO is the total content of BaO, SrO, CaO and MgO.
10. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: (SiO2+Al2O3+ZrO2) / (Rn2O+RO) is 1.0-2.2; and / or (SiO2+B2O3+ZrO2) / Rn2O is 1.4-2.7, wherein Rn2O is the total content of Li2O, Na2O and K2O, and RO is the total content of BaO, SrO, CaO and MgO.
11. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: SiO2+B2O3+Al2O3: 45-60%; and / or ZrO2: 2.5-8.5%; and / or Nb2O5: 6-9.91%; and / or Li2O: 7.5-30%; and / or Na2O: 7.5-22%; and / or BaO: 0-2.5%; and / or SrO: 0-3.5%; and / or CaO: 0-10.5%; and / or Mg O: 0~5.5%; and / or ZnO: 0~4.5%; and / or La2O3: 0~1.5%; and / or Gd2O3: 0~1%; and / or Y2O3: 0~1.5%; and / or Yb2O3: 0~1%; and / or TiO2: 0~6.5%; and / or WO3: 0~2%; and / or Ta2O5: 0~2%; and / or K2O: 0~6%; and / or Sb2O3: 0~0.25%.
12. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, among which: ZrO2: 3-7.5%; and / or Nb2O5: 7-9.91%; and / or Li2O: 12-23%; and / or Na2O: 10.5-18.5%; and / or BaO: 0-1%; and / or CaO: 0-7%; and / or ZnO: 0-2%; and / or TiO2: 0-4%; and / or K2O: 0-4%; and / or Sb2O3: 0-0.1%.
13. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, among which: Al2O3: 0~7%.
14. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in molar percentage, wherein: SiO2: 36-54%; and / or B2O3: 5.5-14%; and / or Al2O3: 0-4%.
15. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in molar percentage, wherein: SiO2: 40-49%; and / or B2O3: 6.5-12%.
16. The optical glass according to any one of claims 1 to 4, characterized in that: Its components do not contain Al2O3; and / or do not contain SrO; and / or do not contain MgO; and / or do not contain La2O3; and / or do not contain Gd2O3; and / or do not contain Y2O3; and / or do not contain Yb2O3; and / or do not contain WO3; and / or do not contain Bi2O5; and / or do not contain Ta2O5.
17. The optical glass according to any one of claims 1 to 2, characterized in that: The refractive index n of the optical glass d 1.62~1.78; Abbe number v d It is 34 to 44.
18. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.64~1.75; Abbe number v d It is 35 to 42.
19. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.66~1.70; Abbe number v d It is 36 to 40.
20. The optical glass according to any one of claims 1 to 4, characterized in that: The relative partial dispersion deviation value △P of the optical glass g,F is below -0.00300; and / or the density ρ of the optical glass is 3.25 g / cm 3 and / or the number A of optical glass crystals is 5 or less.
21. The optical glass according to any one of claims 1 to 4, characterized in that: The relative partial dispersion deviation value △P of the optical glass g,F is below -0.00350; and / or the density ρ of the optical glass is 3.15 g / cm 3 and / or the number A of optical glass crystals is less than 2.
22. The optical glass according to any one of claims 1 to 4, characterized in that: The relative partial dispersion deviation value △P of the optical glass g,F is below -0.00410; and / or the density ρ of the optical glass is 3.05 g / cm 3 Below; and / or the number A of optical glass crystallizations is 0.
23. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 22.
24. An optical element, characterized in that It is made of the optical glass described in any one of claims 1 to 22, or is made of the glass preform described in claim 23.
25. An optical instrument, characterized in that Containing the optical glass according to any one of claims 1 to 22, and / or containing the optical element according to claim 24.
Citation Information
Patent Citations
Optical glass, glass prefabricated part and optical element
CN112142324A